Extraction of gelatin from fish wastes for use in diets for the goldfish Carassius auratus - Al-Noor et al. (Iraqi Journal of Aquaculture, 2025)
The current study aimed to extract gelatin from the skins of the oriental sole Brachirus orientalis using a chemical method. The chemical composition of the extracted gelatin showed a moisture content of 9.66%, a high protein content of 86.11%, a fat content of 1.44%, and an ash content of 2.69%. The results of amino acid analysis of the gelatin protein indicated the presence of 17 amino acids. The highest concentration was for threonine at 72.13 mg/g and glutamic acid at 89.79 mg/g, while lysine and aspartic acid had the lowest concentrations at 18.72 mg/g and 10.44 mg/g, respectively. The results showed a variation in the chemical composition between the different diets. The highest protein content was observed in the T3 diet, with a value of 31.91%, compared to the other treatments C, T1, and T2, which recorded values of 30.25%, 30.74%, and 31.52%, respectively. The highest values for final weight, total weight gain, daily growth, specific growth rate, relative growth, and feed conversion ratio were recorded in the T3 diet, with values of 171.79 g, 84.86 g, 1.13 g/day, 4.02%/day, 1.30%, and 3.21, respectively. The lowest values for these parameters were observed in the control diet C, with values of 131.97 g, 45.09 g, 0.60 g/day, 2.71%/day, 0.69%, and 5.24, respectively. The results demonstrated that the use of gelatin in T1, T2, and T3 diets provided good growth compared to the control diet, which lacked gelatin addition. The T3 diet outperformed all other diets in growth parameters, indicating the success of using protein products in fish diet across all treatments. However, the T3 diet was the best, with a significant difference (P < 0.05) compared to other treatments. The T3 diet also showed the best physical properties (density, buoyancy, sinking speed, and disintegration) compared to the other diets. Statistical analysis revealed significant differences between treatments (P < 0.05).